2010
DOI: 10.1021/jp104660a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photocatalytic Activity and Ferromagnetism in Gd Doped BiFeO3 Nanoparticles

Abstract: BiFeO 3 (BFO) is of considerable interest because of its potential applications in the design of devices combining magnetic, electronic, and optical functionalities. Effects of the Gd dopant on the structural, photocatalytic activity, and ferromagnetic properties of BFO nanoparticles have been studied. X-ray diffraction and Raman spectra results of Bi 1-x Gd x FeO 3 (BGFO x , x ) 0, 0.05, 0.1, and 0.15) reflect that the crystal structure of the samples remain stable for x < 0.1, while compositional-driven phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
158
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(168 citation statements)
references
References 33 publications
7
158
3
Order By: Relevance
“…In spite of this complex magnetic behavior, this compound has a great potential for information storage, sensors, and electric field controlled devices. It has been shown that by substitution of elements at the A-site (Bi) or B-site (Fe), the SSMS can be suppressed and, therefore, enhancement of the magnetic properties is evidenced [6][7][8][9][10][11][12][13][14][15]. Rare-earth elements (La, Nd, Eu, Dy, Gd, Ho, Y, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this complex magnetic behavior, this compound has a great potential for information storage, sensors, and electric field controlled devices. It has been shown that by substitution of elements at the A-site (Bi) or B-site (Fe), the SSMS can be suppressed and, therefore, enhancement of the magnetic properties is evidenced [6][7][8][9][10][11][12][13][14][15]. Rare-earth elements (La, Nd, Eu, Dy, Gd, Ho, Y, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Improved and interesting magnetic properties have been found in pure and doped BiFeO3 nanoparticles prepared by different methods. [20][21][22][23] Visible light photocatalytic properties have been seen in BFO nanoparticles. 24 Microwave absorption properties of BiFeO 3 nanoparticles have been found to be better than those of bulk BFO.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Guo et al reported an enhanced photocatalytic activity in Gd-doped BFO nanoparticles by degrading rhodamine B (RhB) under visible light illumination. [20] Di et al synthesised BFO samples with different morphologies by hydrothermal method and decorated BFO particles with Ag. They showed an enhancement of RhB degradation by Ag-decorated BFO compared to undecorated BFO under simulated sunlight.…”
Section: Cmentioning
confidence: 99%